Two Stubborn Storage Insect Pests, Callosobruchus maculatus and Sitophilus zeamais: Biology, Food Security Problems and Control Strategies - Nwosu, Luke C; Azeez, Owolabi M; Eluwa, Akubuike N; Petgrave, Godfrey M (International Research Journal of Insect Sciences, 2020)
This review work contributes to the biology, food security problems and control strategies of two stubborn storage insect pests, the cowpea bruchid (Callosobruchus maculatus Fabricius) and the maize weevil (Sitophilus zeamais Motschulsky). The beetles have high destructive capacity and therefore require control tactics that are rapidly effective and at the same time safe for man and his environment. The biology will evoke inspirations to devise efficient control tactics. The C. maculatus adult is small and measures 2.5 to 3.5 mm in length, compact, brownish, possesses serrated and un-clubbed antennae, relatively long legs, a pair of distinct and toothed ridges on the ventral side of each hind femur. Whereas, S. zeamais adult measures between 3.0 to 3.5 mm long and it is easily identified by its prominent protruded snout or rostrum. Cowpea varieties most common for C. maculatus to lay their eggs are black eyed peas, mung beans and adzuki bean and when more than one host is available; the insect chooses its host depending on the variety- size of the bean and texture of the seed coat. It was revealed that under certain storage conditions, S. zeamais shows preference to products which are not maize. Application of the efficient control tactics will ensure food security of cowpea seeds and maize grains in storage.